Оцінка ефективності інвестицій в енергозбереження на підприємствах ПЕК - Пономарьов, С. В. (НТУ "ХПІ", 2012)
У статті оцінено ефективність інвестицій в енергозбереження (на прикладі Харківської ТЕЦ-5). Визначено переваги та недоліки чинних методик оцінки ефективності капіталовкладень в енергетику, обґрунтовано напрями удосконалення чинних методик.

Efficiency of investments in energy-savings (on Kharkiv Combined Heat and Power Plant № 5 information) is appraised in the article. The advantages and failings of estimation capital investments in energy efficiency by operating methods are curtained, the directions of operating methods improvement are grounded.
Еstimation of investments efficiency in energy-savings on power and fuel enterprises
Keywords: капіталовкладення; чинні методики; капіталоємність; енергоносії; енергоринок; гідромуфти; перетворювачі частот; модернізація